INTERNASIONALISASI KONFLIK INTERNAL KELOMPOK SEPARATISME EUSKADI TA ASKATASUNA (ETA) DI SPANYOL - Sekar Sari, Afifah Veriyana; Pattipelohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Euskadi Ta Askatasuna (ETA) was originally only a discussion group for students at Deusto University. However, as a result of dictatorial leadership and discriminatory attitudes adopted by General Fransisco Franco, the ETA group was created as a group that carried out all kinds of acts of violence, aimed at liberating the Basque Country. The act of separatism carried out by ETA separatist groups has become a threat to the Spanish state. Various negotiations have been carried out by the Spanish Government in order to build peace in their relations, but have not been able to end internal conflicts that occurred in the country which is a member state of the European Union. One of the strengths of the ETA separatism group comes from the relationship that exists between the ETA separatism group and terrorist groups from other countries that entered the international network. In this study, the author use the theories: Protracted Social Conflict, Conflict Internationalization, and Sources of Contemporary Conflict to explain that internal conflicts that have occurred for more than 50 years are due to the desire of the Basque Country to separate from the Spanish state. The research method used is qualitative which is carried out by collecting and analyzing data, to find out the reasons for internal conflicts between ETA separatism groups and the Government has not been able to find a way of peace.